Performance of Transition-Sensitive Models in Predicting Flow Structures over Delta Wings - Elkhoury, Michel (2015)
Laminar-turbulent transition may have considerable influence on the performance of moderate and high-speed aerodynamic vehicles. The two recently developed transition-sensitive models, SST-TR and , are employed to assess their abilities in resolving the complex underlying flow physics associated with flow structures over delta wings. In particular, their capabilities in capturing the aerodynamic characteristics of three-dimensional flow associated with vortex breakdown, shear-layer instabilities, and boundary-layer transition are assessed. These closures are employed to simulate vortex breakdown and near-wall flow structures over a delta wing planform with a moderate sweep angle of 50 deg at a Reynolds number of [Math Processing Error], where a combination of laminar, transitional, and turbulent flowfields coexist. Accuracy of these models in predicting boundary-layer transition adjacent to a delta wing surface with a high-sweep angle of 70 deg and Reynolds numbers of [Math Processing Error] and [Math Processing Error] is investigated. Large-eddy simulation with dynamic Smagorinsky subgrid scale model is also employed to assess its capability in predicting transition on delta wing planforms. All numerical simulations are compared with available experimental data found in the literature.